Kobiety radzieckiego samizdatu we współczesnej kulturze rosyjskiej — skomplikowane drogi feministek drugiej fali - Mendrela, Karolina (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article aims to reconstruct the history of women who created female Soviet samizdat Woman and Russia and magazine Maria. They are examples of a postsoviet woman who needs to find a place for herself in the new Russian reality after the fall of the Eastern Block. Despite her experience in dissident activity she cannot find her place in the new women`s movement in Russia. The Russian women’s movement in 90’s had two main sources: women organizations originating from the Soviet times and the Russian feminist research institutes, which were cooperating with Western feminist organizations. Despite big popularity of women`s organization in the beginning nowadays Russia has got a problem with poor social and political activity of Russian women. The author of the article indicates several reasons for such a situation.